2017
DOI: 10.1038/srep43939
|View full text |Cite
|
Sign up to set email alerts
|

SNP-SNP interactions between WNT4 and WNT5A were associated with obesity related traits in Han Chinese Population

Abstract: Considering the biological roles of WNT4 and WNT5A involved in adipogenesis, we aimed to investigate whether SNPs in WNT4 and WNT5A contribute to obesity related traits in Han Chinese population. Targeted genomic sequence for WNT4 and WNT5A was determined in 100 Han Chinese subjects and tag SNPs were selected. Both single SNP and SNP × SNP interaction association analyses with body mass index (BMI) were evaluated in the 100 subjects and another independent sample of 1,627 Han Chinese subjects. Meta-analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…To date, fewer studies have examined the effects of interactions on obesity. Despite this, some obesity-related interactions still have been found, including PRKD1 - FTO and WNT4 - WNT5A (Wei et al, 2012; Young et al, 2016; Dong et al, 2017). Pathway-based analysis is an alternative approach to detect gene interactions.…”
Section: Discussionmentioning
confidence: 99%
“…To date, fewer studies have examined the effects of interactions on obesity. Despite this, some obesity-related interactions still have been found, including PRKD1 - FTO and WNT4 - WNT5A (Wei et al, 2012; Young et al, 2016; Dong et al, 2017). Pathway-based analysis is an alternative approach to detect gene interactions.…”
Section: Discussionmentioning
confidence: 99%
“…There are two studies showing that SNPs of the Wnt4 gene can affect its expression and function. SNP rs7521902 in Wnt4 is significantly correlated with the pathogenesis of endometriosis (Angioni et al, 2020), and rs2072920 in Wnt4 is associated with body mass index (BMI) variations in the Han Chinese population (Dong et al, 2017). We identified the critical regions of the Wnt4 promoter which contained a SNP -3015 (G > C) and we showed that SNP -3015 (G > C) in the Wnt4 gene was significantly associated with keel length and comb length in chickens, the individuals with CG genotype having a longer keel length.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, we speculated that the interaction of rs807181 and 807183 affected the ATG4A gene and down-regulated or inhibited its role in autophagy, which led to an increased susceptibility and ability of HPV to bind to the host. Some studies have shown that SNP-SNP interactions were notably associated with BMI ( 30 , 31 ), as well as colon cancer. The association between ATG4A genetic variations and HPV infection is still unknown.…”
Section: Discussionmentioning
confidence: 99%